Promoting breastfeeding practices among Thai-employed mothers - Susanha Yimyam (2018)
Increasing woman's participation in the labor force is frequently attributed for thelow rate and duration of breastfeeding. Rapid development and social change mightthreaten the conflicts between women's productive and reproductive roles. Women havea right to offer optimum nutrition to their babies through breastfeeding; they also areentitled to seek gainful employment. To manage these work-family conflicts, womenneed various help and support. This challenge to develop breastfeeding promotionintervention includes health policy formulation and health care services as well as familyand workplace support.This chapter reviews the interventions to promote breastfeeding for mothersemployed outside the home. It discusses how women combine breastfeeding withemployment, the importance of ongoing breastfeeding support following delivery, and anexample of a successful breastfeeding promotion program for full-time outside workingmothers based on our studies. Our study first focused on breastfeeding education andsupport conducted by health care providers. It reveals that breastfeeding education duringthe first few days in the hospital was insufficient. During the following weeks, mostmothers needed support for breast engorgement and perceived breast milk insufficiency.Breastfeeding rates at four months (both exclusive breastfeeding and breastfeeding withformula) among mothers receiving breastfeeding education and follow-up visits weresignificantly higher than for those receiving routine care. Furthermore, the next studyaimed to develop breastfeeding support at the workplace. It found that implementationsof a breastfeeding corner and workplace support campaigns are necessary for full-timeemployed mothers. Breastfeeding rates six months after these implementations were significantly higher than rates before, both for exclusive breastfeeding and breastfeedingwith formula. Suggestions for implementing successful breastfeeding campaigns for full-timeemployed mothers are provided. Breastfeeding promotion programs should be integratedon multiple levels such as personal (mother), communities (family and workplace), andnational (policy), and include education and guides for combining breastfeeding withemployment, enhancing family and workplace supports, and maternal and child friendlypolicies. © 2013 Nova Science Publishers, Inc. All rights reserved.